2003
DOI: 10.3108/beej.2003.01010009
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Factors Affecting Computer-Based Learning in Haemostasis: A Cultural Experience

Abstract: Computer based learning (CBL) is increasingly used to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Learners need motivation to learn. Most of the studies that investigated the influence of students' motivation on efficacy of CBL reported that student intrinsic and extrinsic motivation contributes to the success of CBL (Ganotice et al, 2019;Overfield & Bryan-Lluka, 2013;Higgins et al, 2019). Furthermore, findings from the retrieved papers included in this review revealed that students motivation may be the catalyst required for CBL to be effective (Higgins et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Learners need motivation to learn. Most of the studies that investigated the influence of students' motivation on efficacy of CBL reported that student intrinsic and extrinsic motivation contributes to the success of CBL (Ganotice et al, 2019;Overfield & Bryan-Lluka, 2013;Higgins et al, 2019). Furthermore, findings from the retrieved papers included in this review revealed that students motivation may be the catalyst required for CBL to be effective (Higgins et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Para mahasiswa yang kreatif berusaha mengatasi kelemahan penguasaan bahasa tersebut dengan mengalihkan eksplorasi ke situs penyedia animasi dan gambar/grafik. Tampilan seperti ini telah diakui sejumlah peneliti dapat menimbulkan kesenangan belajar peserta didik (Overfield & Bryan-Lluka, 2003;Gunn & Pitt, 2003;White et al, 2001). Berdasarkan pantauan melalui forum diskusi, cara yang dilakukan makahsiswa tersebut sedikitnya telah dapat memecahkan permasalahan bahasa.…”
Section: Gambar 1 Grafik Respons Mahasiswa Terhadap Genetikunclassified
“…Faced with the changing realities of undergraduate life, students have become increasingly strategic with their use of time due to a number of competing demands such as parttime work (MacFarlane, 1992). The perceived relevance of online material is an important factor in student engagement (Overfield and Bryan-Lluka, 2003). In a study of the effectiveness of a variety of computer-based learning packages, it was found that a self-assessment quiz was little used in the first 14 weeks of teaching and just over half the class used it in the three weeks leading up to the end of module exam (Gunn and Pitt, 2003).…”
Section: Introductionmentioning
confidence: 99%